(untitled) (Journal of Eye Movement Research, 2015)
This study investigated the correlations between the form features and legibility of Chinese characters by employing the eye tracking method in two experiments: Experiment 1 examined factors affecting Chinese character legibility with character modules and identified the correlations between character form and legibility of crossing strokes; and Experiment 2 examined the effect of crossing strokes on subjective complicacy perception in both Chinese characters and English letters. This study determined that enclosed Chinese characters affect subjective complicacy perception and reduce saccadic amplitude. In addition, greater number of stroke crossings produced higher subjective complicacy perceived for both Chinese characters and English letters. The results of this study serve as a reference for predicting Chinese character legibility and assessing type design superiority.